2022
DOI: 10.3390/jcm11164922
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Survival in Patients with Peritoneal Metastasis from Colorectal Cancer

Abstract: Objectives: The aim of this study was to analyze the prognostic factors of survival in patients with peritoneal metastasis (PM) from colorectal cancer (CRC). The type of relationship between survival and the PM time of detection was used to determine whether it was synchronous with the primary tumor or metachronous. Patients and Methods: Retrospective observational study. It included patients treated for colorectal adenocarcinoma diagnosed between January 2005 and December 2019 who presented PM at the time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Studies that have found an association between KRAS mutations and OS are more likely to have recruited patients with metastatic colorectal cancer rather than early-stage cancer. For instance, Mendoza-Moreno et al found that at 36 months more patients with peritoneal metastases and KRASwt tumours were alive compared to KRASmut (31% vs. 15%; p < 0.001) [40]. Alkader et al found a similar association of shorter overall survival in KRASmut when compared to KRASwt patients (21 months vs. 17 months) [41].…”
Section: Discussionmentioning
confidence: 97%
“…Studies that have found an association between KRAS mutations and OS are more likely to have recruited patients with metastatic colorectal cancer rather than early-stage cancer. For instance, Mendoza-Moreno et al found that at 36 months more patients with peritoneal metastases and KRASwt tumours were alive compared to KRASmut (31% vs. 15%; p < 0.001) [40]. Alkader et al found a similar association of shorter overall survival in KRASmut when compared to KRASwt patients (21 months vs. 17 months) [41].…”
Section: Discussionmentioning
confidence: 97%
“…28 Studies have found peritoneal metastasis to be an independent prognostic factor for advanced CRC. 29 As a tumor-specific location, no definite trial on PM for testing systemic chemotherapy for CRC has been reported. A recent publication reported a mean survival for patients having PM of 16.3 (13.5-18.8) months compared with 19.1 (18.3-19.8) months for patients having liver isolated metastasis.…”
mentioning
confidence: 99%